Ghost in the criminal justice machine: reform, white supremacy, and an abolitionist future - DeWeaver, Emile Suotonye (The New Press, 2025)
"An activist, essayist, and organizer draws from his personal experience of imprisonment to interrogate the premises of prison reform efforts"--